ANALISA DAN PERENCANAAN PENINGKATAN JALAN ALTERNATIF MANYARAN – MIJEN - Bima Prahar Aldilase; Sahil Riskie Tamara; Moga Narayudha; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2014)
Semarang city as a center of activity will always face problems which require the movement of vehicles and infrastructure facilities. Therefore need to model the movement on route choice in urban road network. By knowing the route choice models can be seen in the new alternative road network which is parallel to and travel time / travel costs are lower , then the riders tend to use the new road. In this study conducted at Mijen area road network. Road Manyaran – Mijen is one of the most important because of it’s function as a alternative road that connects subdistrict Manyaran with subdistrict Mijen. The results of the Analysis and Upgrade Design Alternative Road Manyaran – Mijen with 10 years design life, the value of the existing DS (Degree of Saturation) = 0,75, therfore it must improve the road by widening of 6 meters to 7 meters by 2 meters shoulder (2/2UD) and overlay. And also change the area of flexible pavement fracture with rigid pavement. From the analysis and planning of road improvement Manyaran - Mijen obtained results in the form of construction of the widening of 6 metres to 7 metres and composition of pavement construction for widening Laston height of 10 cm, 15 cm crushed stone class B (CBR 80 %), 20 cm gravel class B (CBR 50 %). While the overlay calculation showed 12 cm (Laston). For planning drainage (channel edge), the form used is rectangular channel. Plan budget for road planning Manyaran - Mijen This is Rp 72.518.550.000,00.